2010
DOI: 10.3109/10903127.2010.497896
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Morphine, Fentanyl, and Methoxyflurane in the Prehospital Setting

Abstract: Inhaled methoxyflurane, IN fentanyl, and IV morphine are all effective analgesic agents in the out-of-hospital setting. Morphine and fentanyl are significantly more effective analgesic agents than methoxyflurane. Morphine appears to be more effective than IN fentanyl; however, the benefit of IV morphine may be offset to some degree by the ability to administer IN fentanyl without the need for IV access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 30 publications
5
66
1
6
Order By: Relevance
“…The mean dose of fentanyl used in our study is in line with the proposed doses in the literature [8,9,[12][13][14][15] including in the specific setting of mountain rescue [2]. The mean dose of intra-nasal fentanyl was lower than when used intravenously, which is partially explained by a significantly higher proportion of paediatric patients in the intranasal group.…”
Section: Analgesic Strategiessupporting
confidence: 73%
“…The mean dose of fentanyl used in our study is in line with the proposed doses in the literature [8,9,[12][13][14][15] including in the specific setting of mountain rescue [2]. The mean dose of intra-nasal fentanyl was lower than when used intravenously, which is partially explained by a significantly higher proportion of paediatric patients in the intranasal group.…”
Section: Analgesic Strategiessupporting
confidence: 73%
“…19,40,41 A number of observational studies in prehospital and emergency department settings have evaluated the efficacy and safety of fentanyl and morphine. [29][30][31][32]42,43,44 These studies uniformly showed that fentanyl and morphine compare favorably to one another in both the reduction of pain and lack of adverse events. In 2006, Kanowitz et al conducted a retrospective chart review of 2,129 patients who were administered fentanyl in an out-of-hospital setting and concluded fentanyl was effective in decreasing pain scores without causing substantial hypotension, respiratory depression, hypoxia, or sedation.…”
Section: Safety and Efficacymentioning
confidence: 99%
“…28,[31][32][33]35 There were few direct comparisons made between IV morphine and IV fentanyl, although a number of studies compared IN fentanyl with IM or IV morphine. [29][30][31][32]36 Intravenous administration was the most commonly researched route for fentanyl, but in a few observational studies, intranasal delivery appeared to be safe, effective, and less painful than intravenous cannulation. 36 While the panel acknowledges the potential value of administering analgesia via intraosseous access, there was little evidence in the prehospital literature to inform a recommendation.…”
Section: Routesmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing formulations for IN fentanyl have been developed [199], but the overall efficacy results are similar: IN fentanyl data are incomplete but the approach has promise for a variety of patient types [200][201][202]. It appears possible that, while the analgesic efficacy may not match that of IV morphine, the ease of administration may render IN fentanyl (one commonly used dose is 1.5 mcg/kg via atomizer) a viable option in some situations [203]. While there are some preliminary data on IN fentanyl use, the state of the art for this approach is that it is prime subject matter for clinical research rather than widespread adoption [204].…”
Section: Fentanylmentioning
confidence: 99%